Analisis Keragaman Genetik Acremonium yang Berasosiasi dengan Tanaman Gaharu Menggunakan Teknik Random Amplified Polymorphic DNA (RAPD) - Dewi Rahmawati; Nurita Toruan-Mathius (Jurnal AgroBiogen, 2009)
Agarwoodor gaharu is a plant that has a high economic value in Asia,due to its use for production of incense and traditionalmedicines. The agarwood formation occurs in the trunk androots of trees that have been infected by a fungus, such asAcremonium spp. Various fungi were associated with theagarwood formation. Acremonium is generally considered ashighly polyphyletic, contains distantly related fungi. A studywas done to identify genetic diversities in 10 isolates ofAcremonium spp. from four different areas in Indonesia thatare associated with Aquilaria and Gyrinops verstigii using theRandom Amplified Polymorphic DNA (RAPD) technique.Eight RAPD primers, i.e., OPA 02, OPB 04, OPB 07, OPB 17,OPC 11, OPD 03, OPD 05, and OPE 07 were used in theanalyses. The results indicated that similarity index values ofthe genetic variation ranged from 0.21 to 0.97. Based on theNei and Li’s similarity coefficients, these values indicatingthe presence of high degree of genetic variability. The lowestdegree of genetic similarity were found between isolates F(Acremonium spp., which is associated with G. verstigii fromMataram, Nusa Tenggara Barat), and LM2 from south coastalarea of West Sumatra. The highest genetic similarity value(0.97) was found between isolates Sr2 and Sr4 from Sorong,Papua. Results from the cluster analysis indicated that theisolates could be grouped into two major clusters that wereassociated with their geographical locations.